270 APIGENIN DECREASES HEMIN-MEDIATED HEME OXYGENASE-1 INDUCTION. (1st January 2005) - Abate, A.; Yang, G.; Wong, R. J.; Schroder, H.; Stevenson, D. K.; Dennery, P. A.
Abstract : Hemin is a strong inducer of heme oxygenase-1 (HO-1) expression. The binding of NRF-2 and MafK to the StRE region of HO-1 promoter mediates hemin-induced HO-1 up-regulation. While moderate over-expression of HO-1 is protective against oxidative stress, uncontrolled high levels of HO-1 can be detrimental. Therefore, in order to study the regulation of HO-1 induction, we evaluated the effect of apigenin (APG), a flavonoid, which is potentially involved in a number of phosphorylation pathways and also known to inhibit inducible genes, such as iNOS and COX-2. When mouse embryonic fibroblasts (MEFs) were incubated with APG (10 - 40 μM) and then treated with 30-μM hemin, mRNA expression and HO-1 protein were decreased. Western Blots (Fig. 1 ) show that HO-1 protein expression increased after treatment with hemin, but when cells were pre-incubated with APG or quercetin (QUER) and then stimulated with hemin for 6 h, HO-1 protein levels were significantly inhibited. To assess the effects of APG on HO-1 promoter activity, NIH-3T3-luc cells, stably transfected with a 15-kb mouse HO-1 promoter fused to the reporter gene luciferase, were treated with APG and HO-1 promoter activity was assessed by bioluminescence imaging (BLI). APG significantly reduced the induction of HO-1 promoter activity by hemin. Furthermore, through the use of specific inhibitors, this effect of APG was found unrelated to its PKC, CK2, PI3K, p38, or ERK inhibitory activities. By contrast, QUER (10 - 40 μM), also a flavonoid, imitated the inhibition of HO-1 by APG in cells. In addition, in in vivo studies using HO-1-luc transgenic mice treated with hemin, oral administration of APG (50 mg/kg) decreased HO activity and HO-1 protein expression in the liver. These results suggest that hemin-induced HO-1 expression can be attenuated by APG through a mechanism specific to its flavonoid properties.